1999
DOI: 10.1136/thx.54.12.1070
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of hospital admission with asthma in children aged 5-14 years: relation with road traffic in north west London

Abstract: Background-Evidence for an association between road traYc pollution and asthma is inconclusive. We report a case-control study of hospital admissions for asthma and respiratory illness among children aged 5-14 in relation to proxy markers of traYc related pollution. Methods-The study was based on routine hospital admissions data in 1992/3 and 1993/4 for North Thames (West) health region within the M25 motorway. Cases were defined as emergency admissions for asthma (n = 1380) or all respiratory illness includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 15 publications
3
58
1
Order By: Relevance
“…Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002). Some studies have found an association between traffic volume and the number of hospital admissions for asthma (English et al, 1999), vehicle or truck traffic and self-reported symptoms of asthma (Weiland et al, 1994;Duhme et al, 1996), but others have found no association between asthma and traffic volume (Wilkinson et al, 1999). Truck and road traffic were related to chronic respiratory symptoms and reduced lung function in studies of adolescents (Wjst et al, 1993;Oosterlee et al, 1996;Van Vliet et al, 1997;Brunekreef et al, 1997;Ciccone et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002). Some studies have found an association between traffic volume and the number of hospital admissions for asthma (English et al, 1999), vehicle or truck traffic and self-reported symptoms of asthma (Weiland et al, 1994;Duhme et al, 1996), but others have found no association between asthma and traffic volume (Wilkinson et al, 1999). Truck and road traffic were related to chronic respiratory symptoms and reduced lung function in studies of adolescents (Wjst et al, 1993;Oosterlee et al, 1996;Van Vliet et al, 1997;Brunekreef et al, 1997;Ciccone et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…All but one were conducted in Europe and Asia ( Table 2). Fifteen of these have been in children (96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110), four in adults (111)(112)(113)(114), and one study in both children and adults (115).…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
“…Krämer et al (109) conducted a cross-sectional study of atopic sensitization and asthma diagnosis but had a prospective outcome assessment of atopic symptoms for 1 year along with seasonal NO 2 measurements. Other designs include three case-control studies of hospital admissions (97,99,108), and one case-control study of California Medicaid claims for asthma (105). Another study was a mixture of cross-sectional, surveynested case-control, and historical cohort (110).…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
“…Nuisances perception at home was also suggested as a good proxy for traffic -related air pollution in Switzerland (Oglesby et al, 2000 ). Following the same rationale as the VESTA ''traffic density'' index, some studies combined traffic and distance data (Wilkinson et al, 1999;Pearson et al, 2000). In a recent case -control study of air pollution from traffic and childhood cancer, two cumulated exposure indices were also accommodated, as in the present study, with the same Danish OSPM software that is built in the ExTra model (Raaschou -Nielson et al, 2000;RaaschouNielson et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%